Security analysis and improvement of a certificateless signcryption scheme - Zhen-guo ZHAO (Tongxin xuebao)
To solve the certificate management problem in the traditional public key cryptography and the key escrow problem in the identity-based public key cryptography, Al-Riyami and Paterson proposed the concept of the certificateless public key cryptography.Recently,Zhu et al.proposed a certificateless signcryption without bilinear pairings.However， their scheme was completely insecure against with two concrete attacks. A strongly secure certificateless signcryption without bilinear pairings was also proposed, which was provably secure in the random oracle model under the assumption that the discrete logarithm problem and the computational Diffie-Hellman problems were intractable. Furthermore, the efficiency of the proposed scheme is very high since only four modular exponentiations and five modular exponentiations are needed in the signcryption algoriahm and unsigncryption algorithm separately.